Leveraging Critical Incidents to Enhance In-service Teacher Professional Development: A case study in Temanggung, Central Java - Yesika Windi Resila; Concilianus Laos Mbato (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2024)
The continual development of professional teachers is essential for upholding an ideal learning atmosphere for students. Although there were extensive studies on pre-service training and early career development, there is a gap in information regarding how in-service teachers, who have years of experience, continue to enhance their professionalism throughout their careers. In this study, teachers encountered several unexpected and impactful classroom Critical Incidents, which provided significant insights into their professional development. This study aimed to examine the critical incidents faced by practicing teachers and how these experiences shaped their professional identity. It explores how these moments affect their fundamental values, beliefs, and teaching methods. The research investigated the real-life experiences of three Junior High school in-service teachers in Temanggung, Indonesia by using teacher reflections and conducting in-depth interviews. The findings of the interviews with the in-service teachers indicate that students' attitudes towards teachers and their own mental health were associated with a higher frequency of critical incidents in the classroom. The researchers also discovered that critical incidents were far better for their growth compared only to participating in teacher development training, as it provided valuable experience and exposure to real-world situations. This finding had profound implications both in academia and in practical applications. Teacher education programs can enhance their preparation of pre-service teachers by acknowledging the impact of significant incidents. Furthermore, the results can be used to enhance professional development programs for teachers, enabling them to analyze their critical incidents and use these experiences in their development.